2015
DOI: 10.1111/ijcp.12672
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and end-stage renal disease are risk factors for poor outcomes ofClostridium difficileinfection: a systematic review and meta-analysis

Abstract: BACKGROUND The objective of this systematic review and meta-analysis was to assess the clinical outcomes of Clostridium difficile infection (CDI) in patients with chronic kidney diseases (CKD) and end stage renal disease (ESRD). METHODS A literature search was performed from inception through February 2015. Studies that reported relative risks, odds ratios, or hazard ratios comparing the clinical outcomes of CDI in patients with CKD or ESRD and those without CKD or ESRD were included. Pooled risk ratios (RRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 43 publications
3
22
0
1
Order By: Relevance
“…In overall cohort, 20.3% of the patients experienced initial metronidazole treatment failure, but the failure rate in CKD patients was 16.7%, which was not higher than that in control patients. The clinical features of complicated CDI, such as ileus or toxic megacolon in CKD patients, were also not more frequent than in non-CKD patients, and the incidence of recurrent CDI was not significantly different among groups unlike the previous findings [30,31]. Nevertheless, when compared with CDI patients without CKD, initial metronidazole therapy in those undergoing dialysis tended to be associated with an increased risk of treatment failure.…”
Section: Discussionmentioning
confidence: 56%
“…In overall cohort, 20.3% of the patients experienced initial metronidazole treatment failure, but the failure rate in CKD patients was 16.7%, which was not higher than that in control patients. The clinical features of complicated CDI, such as ileus or toxic megacolon in CKD patients, were also not more frequent than in non-CKD patients, and the incidence of recurrent CDI was not significantly different among groups unlike the previous findings [30,31]. Nevertheless, when compared with CDI patients without CKD, initial metronidazole therapy in those undergoing dialysis tended to be associated with an increased risk of treatment failure.…”
Section: Discussionmentioning
confidence: 56%
“…En esta serie de casos, se detectaron factores relacionados con la infección por C. difficile como la edad avanzada, el uso de antibióticos, la hospitalización previa, el uso de inhibidores de la bomba de protones y la comorbilidad, lo cual concuerda con lo reportado ampliamente en otros estudios (12,(20)(21)(22)(23). En 2001, Fernández-Caniggia, et al, (24) reportaron la edad avanzada, las comorbilidades, la hospitalización, el tratamiento antimicrobiano y la inmunosupresión reciente, como factores asociados a la infección por C. difficile en una serie de 245 pacientes en Argentina (25).…”
Section: Discussionunclassified
“…Moreover, in ten studies, a significantly increased CDI risk was demonstrated in patients with end-stage renal disease (2.63-fold increased risk) [31]. Similarly, a meta-analysis of 19 studies (case-control and 18 cohort studies) showed that patient with CKD have an increased risk of severe or recurrent CDI, and increased CDI mortality risk (1.51-fold, 2.73-fold and 1.76-fold increased risks, respectively) [32]. In another meta-analysis of four cohort studies including 8 million patients, Thongprayoon et al demonstrated an increased mortality risk in non-dialyzed patients with CKD and CKD stage 5d patients with CDI versus those without CDI (1.73-fold and 2.15-fold increased risks, respectively) [33].…”
Section: Clostridium Difficile Infection In Patients Hospitalized In mentioning
confidence: 99%